ANALISIS MAKNA DENOTATIF DAN KONOTATIF BERITA KONFLIK PALESTINA DAN ISRAEL DALAM KABAR BERITA HARIAN KOMPAS.COM EDISI MEI 2021 - Moh. Syamsul Ma’arif; Wardatul Widadt (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2023)
The purpose of this study is to analyze the form of denotative and connotative meanings of the news of the Palestine and Israel conflict in the May 2021 edition of Kompas.com. This type of research is a descriptive qualitative research. The subject of this research is the news of the conflict between Palestine and Israel. The object of this research is the May 2021 edition of Kompas.com. The data collection procedure uses tapping and note-taking techniques. Miles and Huberman model data analysis is data collection, data reduction, data presentation, and conclusion. The denotative and connotative meanings found in the news of the Palestine and Israel conflict in the May 2021 edition contained 90 data. The use of denotative meaning in the news of the Palestine and Israel conflict in the May 2021 edition contains 69 sentences, while the use of connotative meaning is 21 sentences. May 2021 edition. News of the Palestine and Israel conflict in the May 2021 edition, mostly using actual words.